(untitled) (Kathmandu University Medical Journal, 2012)
Background There is growing evidence that inflammation plays an important role in atherogenesis. Several studies have shown that C-reactive protein (CRP), an inflammatory marker, is associated with stroke severity and outcome. But limited studies are there which show the relationship of CRP with early mortality i.e within seven days. Objective To study the association of CRP within 24 hours after acute ischemic stroke onset with severity during admission, types of ischemic stroke and outcome. Methods This cross sectional study was done including 100 consecutive cases of acute ischemic stroke admitted to Neurology center of College of Medical Sciences, Bharatpur (Chitwan), Nepal. The cases were classified as per TOAST classification and severity at admission assessed using National Institutes of Health Stroke Scale. C-reative protein (CRP) level was estimated by latex particle agglutination test. Result Thirteen percent patients expired by 7th day. In the expired group, CRP was positive in 15.3 percent, 15.3 percent and 61.5 percent in patients with lacunar, cardioembolic and large artery atherosclerotic infarction respectively (p 0.19). CRP was positive in all 7 patients (53.8%) who had expired with severe NIHS scale (p 0.004). Conclusion High CRP level is associated with stroke severity at admission and is an independent predictor of early seven day mortality after ischemic stroke DOI: http://dx.doi.org/10.3126/kumj.v9i4.6339 Kathmandu Univ Med J 2011;9(4):252-5